Kajian Gaya Hipster dalam Logo - Sarah Sofia S. Putri; Alvanov Zpalanzani Mansoor; Naomi Haswanto (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
Hipster logo is popular through online interaction among designers. The theme hipster which refers to modernizing old stuffs is becoming a trending logo design style in 2012. Through structural analysis on 12 confirmed logos as hipster logo, this study will depict the significant graphic elements of hipster logo. This study is conducted to identify what makes a logo called hipster logo. This study will also explain the reasons of certain graphic elements works as iconic visual elements of hipster logo. Through structural analysis, this study finds that circular shape, X symbol or X composition of icons, monogram colors, and sans serif type lettermarks are the basic ingredients in making hipster logo. Those graphic elements then added with certain icons such as triangle, 'estimated' or similar texts, and several images which represent activities or things in 1800s will create a perfect hipster logo. But in the end, it is not the trend or style hype which makes a logo will be remembered, but the shared value between company and its logo is.